The New Solutions in the UAE Attribution Rules Between Negativity and Positivity, a Comparative Study With some Arab Legislations - Al-Fadhli, Ahmed Mahmoud (Journal of Legal and Political Studies, 2014)
Solutions developed in the UAE attribution rules between positive and negative We address in this study some rules of attribution contained in civil transactions law of the United Arab Emirates، and concentrate on explaining the rules that created the United Arab Emirates legislature certain innovations، showing his character and distinguishes it from other legislators who drew them the United Arab Emirates legislature rules of attribution. We discussed the positive innovations that made some rules of attribution، the United Arab Emirates is Arabic legislation referred to in the study، and that we should follow the example of the legislator. In addition to discussing the negative innovations، which in turn led to the flaws and weaknesses in certain rules of attribution of United Arab Emirates، which hoped the United Arab Emirates legislature amended to avoid those flaws and weaknesses، to the rules of attribution of perfect justice and discrimination in determining the applicable law in disputes with a foreign element.
Keywords: Legislature; Rule of Attribution; Civil Transaction; Innovations